Maternal and Fetal Outcomes of Gestational Thrombocytopenia - Oğuzhan Günenc; Bahar Taş (Düzce Tıp Fakültesi Dergisi, 2022)
Aim: The study aimed to evaluate maternal and fetal outcomes of gestational thrombocytopenia according to platelet levels. Material and Methods: The cases who were followed up in our clinic between January 2017 and December 2018, who had no additional diseases, who had term deliveries, and who had gestational thrombocytopenia, were screened retrospectively. The pregnant women included in the study were divided into two groups according to their platelet values, ≤70 x103/mm3 and >70 x103/mm3, and the subgroups were analyzed among themselves. The demographic, clinical, and laboratory data of the patients were also compared between the groups. Results: Among the patients with gestational thrombocytopenia, it was found that the birth week was significantly earlier in the group with platelet ≤70 x103/mm3 (p=0.002). When perinatal characteristics were compared between the groups, the birth weight of the infants in the group with platelet ≤70 x103/mm3 was found to be significantly lower than in the other group (p=0.033). APGAR 1st-minute score was found to be significantly decreased in the group with platelet ≤70 x103/mm3 when compared to the other group (p=0.039). Single and multiple regression analyzes were performed on pregnant women with gestational thrombocytopenia. No risk factors that were associated with adverse maternal and perinatal outcomes were detected in the group with platelet values ≤70 x103/mm3. Conclusion: Fetal growth retardation is seen in patients diagnosed with gestational thrombocytopenia and with platelet values below 70 x103/mm3 and their APGAR scores are lower. The premature birth rate is higher in the same patient group.